22.01: Fire and seismic assessment of an existing steel‐concrete composite structure. (13th September 2017) - de Silva, Donatella; Nuzzo, Iolanda; Bilotta, Antonio; Losanno, Daniele; Nigro, Emidio; Serino, Giorgio
ABSTRACT: An existing steel‐concrete composite structure is analyzed in order to assess its level of protection against both fire and earthquakes. The building has been designed and built more than thirty years ago, implying that both these hazards may not be adequately verified with respect to the current codes. As concerns the fire protection, intumescent coating (IC) was applied on steel members, while an original passive energy dissipation system was employed against seismic actions. In particular, special devices were introduced to sustain the floors, which are suspended at reticular beams on the top of concrete pillars. A Fire Safety Engineering approach has been adopted to assess the structural resistance to fire. To define the thermal properties of the protective, experimental tests were carried out on the existing IC and a new IC. Moreover, thermomechanical analyses of the existing steel structure were carried out, under different fire scenarios, selected according to the fire risk of the different occupancy class of the structure. Non‐linearities and large displacements effects were taken into account. The seismic structural response has been investigated by implementing a dynamic nonlinear analysis according to the current Italian Code. In particular the seismic passive protection system, consisting in dissipative hysteretic devices combined with isolators, has been modelled as a parallel elastic and elasto‐plastic springs' system. Mechanical parameters adopted for the analyses are the result of a wide bibliography study.